Energising the political movements in developing countries: The role of social media. (October 2014) - Sorour, M. Karim; Lal Dey, Bidit
Social media-led mass movements have dominated news headlines in recent times. The success stories of the Occupy movements, anti-globalisation demonstrations in the West, mass protests at Tahrir Square in Cairo and Taksim Square in Istanbul, demonstrations against sexual harassment in Delhi and the Shahbag Square uprising in Dhaka all underpin the fact that in both developed and developing societies, social media can potentially play an important role in organising large scale socio-political events. This 'Behind the News' article reflects on and analyses the recent 'social-media-led' political eruptions in two developing countries, Egypt and Bangladesh.